Early farming communities in northern Transkei: the evidence from Ntsitsana and adjacent areas - Prins, F. E.; Granger, J. E. (Southern African Humanities, 2021)
Archaeological investigations were made of early farming settlement along the middle reaches of the Mzimvubu River, Transkei. A first-millennium site, Ntsitsana, excavated and two occupational phases dated to ca. AD 660 and AD 770 have been identified. Ceramics associated with these phases are typologically similar to coeval ceramics of early farming settlement in Natal, although local differences are evident. Other cultural remains retrieved and described include broken figurines, stone artefacts, grinders, and slag. The spatial patterning on Ntsitsana and another unexcavated farming settlement, known as Ncabela, allows inferences regarding marriage rules and the status of wives within these societies. It is argued, with reference to the patterning of typologically compatible sites along the middle reaches of the Mzimvubu River, that these early agriculturists had a relatively complex political system. To cite this paper: Prins, F.E. & Granger, J.E. 1993. Early farming communities in northern Transkei: the evidence from Ntsitsana and adjacent areas. Natal Museum Journal of Humanities 5: 153-74.